An analysis of CO2 emissions and the presence of the environmental Kuznets Curve in East and Southeast Asian countries. - Alviar, Mikela Therese V.; Santos, Maria Isabel Therese A. (Quezon City School of Economics, University of the Philippines Diliman, 2022)
As the climate crisis worsens, it more and more becomes a point of focus for policy actions nationally and internationally. In order to effectively address it, the crisis must be understood holistically and attempts to quantify its causes and effects must account for a variety of factors in our increasingly interconnected, technologically-evolving world. This research aims to analyze the effects of various demographic, socio-economic, and income variables on climate change. As rapidly industrializing countries, this research places East and Southeast Asian nations in focus. Carbon dioxide emissions are used as an indicator of climate change and ecosystem vitality, and selected variables are integrated into the model to obtain an approximation of the Environmental Kuznets Curve (EKC). Through simple regression analyses of cross-section data, the research found that, save for income which is the usual determinant of EKC, none of the independent variables had sufficient statistical significance in relation to CO2 emissions. The variable representing urban population yielded the highest coefficient, and may thus be considered for policy targeting CO2 reduction. A time series analysis of the Philippines, conducted to confirm the cross-section analysis, produced mixed results. Curves for both regressions were constructed, and although most time series plots did not corroborate those of the cross-section, all regression results were substantiated. Urban population in both regressions and corresponding graphs emerged with an expected inverted U-shaped scatter plot, and can thus be used as a strong substitute for income in the construction of an Environmental Kuznets Curve.
Thesis (BS Economics) - - University of the Philippines Diliman
Includes bibliographical references.
Keywords: Climate change -- East Asian Countries; Climate change -- Southeast Asian Countries; Carbon Dioxide Emissions -- East Asian Countries; Carbon Dioxide Emissions -- Southeast Asian Countries